Adsorption and Fibrillization of Islet Amyloid Polypeptide at Self-Assembled Monolayers Studied by QCM-D, AFM, and PM-IRRAS - Hajiraissi, Roozbeh (Langmuir : the ACS journal of surfaces and colloids, 2018)
Aggregation and fibrillization of human islet amyloid polypeptide (hIAPP) plays an important role in the development of type 2 diabetes mellitus. Understanding the interaction of hIAPP with interfaces such as cell membranes at a molecular level therefore represents an important step toward new therapies. Here, we investigate the fibrillization of hIAPP at different self-assembled alkanethiol monolayers (SAMs) by quartz crystal microbalance with dissipation monitoring (QCM-D), atomic force microscopy (AFM), and polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS). We find that hydrophobic interactions with the CH3-terminated SAM tend to retard hIAPP fibrillization compared to the carboxylic acid-terminated SAM where attractive electrostatic interactions lead to the formation of a three-dimensional network of interwoven fibrils. At the hydroxyl- and amino-terminated SAMs, fibrillization appears to be governed by hydrogen bonding between the peptide and the terminating groups which may even overcome electrostatic repulsion. These results thus provide fundamental insights into the molecular mechanisms governing amyloid assembly at interfaces